KEPEMIMPINAN KEPALA SEKOLAH EFEKTIF ERA PERDAGANGAN BEBAS - Mardiyani, Ani (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2010)
Liberalization of higher education primary education which led the General Agreement on Trade in Services (GATS) WTO can not be avoided anymore, because the world has agreed to free trade in services. There are 12 service sectors including the education.Speaking of school education, then the principal has an important role. Principal in addition shall perform their tasks as teachers, also holds the mandate as the helm of the school; Because on one hand the school principal as an educator, but also as a manager, as a leader, a mentor or supervisor, as a regulator, as the creator of the climate, as an administrator, as mediator, and as a reformer or an innovator. The school principal is a strategic position, as the top leader in schools it has an important role in bringing change and renewal in schools in order to effectively achieve the goal efficiently. In the era of regional autonomy, effective school leadership is necessary, because the effective performance of school principals will be able to empower the school community including teachers, staff, and students, and can promote the activities associated with the outside world including the surrounding community, business industry, figures community and school committees, and the government, so as to improve the quality of schools. Quality include the quality of the context, process inputs, outputs, and outcomes.There are standards of the principal, several criteria, the nature and attitude that must be owned by a school principal so that they can effectively play a role in an optimal way and to achieve optimal results, especially in the era of free trade.